Penguatan Budaya Kerja Islami Melalui Disiplin, Ihsan, Etos Kerja, dan Ta’awun untuk Meningkatkan Kinerja SDM Pendidikan - Dinda Putri Azmalasari; Haris Riadi; Widya Putri Lestari (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to examine the ethics of conflict management and discipline in educational institutions through a literature review approach. Educational institutions, as spaces of social interaction, are inherently prone to conflicts arising from differences in interests, values, and perceptions among individuals. On the other hand, discipline plays a crucial role in maintaining order and supporting the learning process. However, conflict management and the implementation of discipline that are not grounded in ethical principles may lead to further problems within the educational environment. This study employs a descriptive-analytical method by collecting data from various sources, including books, academic journals, and relevant articles. The findings indicate that ethics plays a fundamental role as a foundation for managing conflict and discipline in a fair, wise, and humane manner. An ethical approach can promote constructive conflict resolution and the implementation of discipline oriented toward character development. Therefore, the integration of ethical values in conflict management and discipline is essential to create a harmonious and conducive educational environment.